Emoções martiriais em Alandalus: os mártires voluntários de Córdoba (século IX) - Milhomem, Thiago Damasceno Pinto (2023)
Between the years 850 and 859, 50 Christians were executed by the Islamic government of the Emirate of Córdoba (756/138 H.-912/300 H.). This group of criminals, from an Islamic legal point of view, was composed of subjects of different functions and social strata: men and women, secular people, monks and nuns, former public officials of the emirate and their sons or daughters. They were part of Cordoba society that witnessed the consolidation of Islamic power and the growing prestige of the Arabic language and culture in Alandalus. His crimes were of two types: public insults to the figure of the Prophet Muḥammad (istiḫfaf) and apostasy to the Islamic faith (ridda), both punishable by death. Other Christian supporters of these acts considered their executed co-religionists as martyrs and saints, and their actions as voluntary martyrdoms and a justifiable form of protest. Among the defenders of martyrdom were the priest Eulógio (ca. 800-859) and the secular Paulo Álvaro (died around 861). Both wrote apologetic works for the martyrdoms, in a polemical tone, condemning both Muslims and Christians against the martyrs. From the theoretical fields of History and Anthropology of Emotions, among others, and methodologies such as external and internal criticism of documents, structural, philosophical and imaginative hermeneutics, the works Memorial de los Santos (851-856), Epístolas (851), Documento Martirial (851), Apologético de los Mártires (857) e Pasión de los Santos Mártires Jorge el Monje, Aurelio y Natalia (858) by Eulógio de Córdoba, and Vida de San Eulogio (860), by Álvaro de Córdoba . In these hagiographies, the two Christian authors associated positive emotions such as joy and serenity with martyrs and negative emotions such as anger and hatred with Muslims. Thus, Eulógio and Álvaro condemned the Muslims and legitimized the Christian martyrs through a speech focused on emotions.